A Systematic Review on Visual Sensory of Children Towards City Landmarks - David Ricardo; Galuh Fajarwati; Adelia Matondang (Universitas Atma Jaya Yogyakarta, 2025)
Children's visual sensory of city landmarks is interesting because it has a different perspective than adults or teenagers. High curiosity about something made the preferred landmarks and chosen focus different for each child's age. It does not have to be a prominent city landmark like a monument; even landscapes have become interesting for children to visit. The problem is how many papers discuss this and the resulting children's visual sensory issues. The purpose of this study was to review as many papers as possible to explore the objects of preferred city landmarks and the responses obtained. The method used was to collect various documents from Google Scholar with Publish or Perish and Vos Viewer based on keywords about children's visual sensory of city landmarks, a total of 25 papers to be described in table form to see the essence of the research, the country conducting the study and the year of the study. Then, the paper's contents, such as methods, landmark objects, memory responses, and age groups, were reviewed. The result is that the landscape has become a widely studied place, and technology has begun to create landmarks virtually, using EEG tools, eye trackers, and game engines.